Morphofunctional state of the liver of rat progeny from mothers, infected with Esherichia Coli (experimental research). - Markovskiy, V. D.; Sakal, A. A. (Морфологія / Morphologia / Morfologìâ, 2016)
Background: As a result of extensive and sometimes uncontrolled use of antibacterial drugs the role of conditionally pathogenic microbiota in the development of inflammatory processes significantly increased. An important problem is infections caused by conditionally pathogenic microflora in pregnant women, especially important role of E.coli. Our study of morphofunctional state of progeny liver from mothers with infections caused by Escherichia coli, will clarify special features of infection impact on fetus liver. Objective: to identify morphological and functional features of liver of fetuses, who were born from mothers with prolonged subacute infectious process caused by Escherichia coli. Methods: In order to detect morphofunctional state of the liver of rat fetuses, from mothers, who were infected by Escherichia coli, we conducted two experiments: modeling of chronic intrauterine hypoxia (CIH) and modeling of infection. The experimental material was divided into three groups: control group, group with chronic intrauterine hypoxia - CIH and main group – infected by Escherichia coli. Results: In our study we revealed significant differences between control group and CIH group, as well as between the main group and CIH group. In CIH group liver we found: signs of edema, central venous congestion with hemorrhages in center of lobules. Hepatocytes were in condition of protein dystrophy, sometimes we identified foci of necrosis, which is likely due to influence of hypoxia. In main group we identified the following morphological changes: edema, hyaline droplet degeneration of hepatocytes, also we found, hyperchromatic vacuolated cytoplasm, sometimes we determined non-nuclear, necrotic cells and also we found hepatocytes with larger hyperchromatic nuclei. In liver cells we noticed the increase of degenerative changes accompanied by severe edema of stroma. Conclusion: When mother is infected by Escherichia coli in her offsprings liver we can see developing of alterative changes manifested by dystrophy and necrobiosis of hepatocytes, violation of structure of hepatic lobules on the background of moderately severe compensatory and adaptive processes.